Variation of Particle Pretreatment of Subterranean Termite Attack on Particle Board From Oil Palm Trunk Waste with Phenol Formaldehyde Adhesive - Guido Simbolon; Rudi Hartono; Tito Sucipto; Apri Heri Iswanto (Peronema Forestry Science Journal, 2014)
These research were to known the particle pretreatment on the durability properties of particleboard on termites attack. The variation of particle pretreatment in this research were done by soaking the particle in hot water (1,2 and 3 hours) and cold water (24, 48 and 72 hours). The particle board was made from oil palm trunk using of phenol formaldehyde adhesive with size 30 cm x 30 cm x 1 cm and density target of 0.7 g/cm3. Particle board will be test by grave yard test along 100 days for durability from termites attack and will be compared by Indonesia National Standard (SNI) 01-7202-2006. The result showed that the weight loss of particle board values were 38.63-88.11%. Based on termites attack level, it was classified as very low durability.Keywords : oil palm trunk, phenol formaldehyde adhesive, particle board, subterranean termite.